YOUTUBE SEBAGAI SOLUSI MEDIA DAKWAH DA’I DI BULAN RAMADAN DALAM MASA PANDEMI COVID 19 - Zidni 'Ilman Nafi'a (Jurnal Dakwah Tabligh, 2021)
Muslims are encouraged by Allah to do da'wah, the holy month of Ramadan is a month full of mercy, the reward of those who worship Him will always be doubled, so that many propaganda events through small assemblies are followed by many people, but in the midst of the rampant pandemic covid, 19 (Corona Virus) clustered propaganda activities can no longer be carried out. Youtube as an online-based mass media has the suitability to be used as a propaganda media amid covid pandemic 19. Trenggalek Ansor Youth Movement as a religious social organization through the internal organization Rijalul Ansor conducts the Koran Online as a form of the sermon in providing religious education to the public. The purpose of this study was to find out YouTube as a preaching da'i solution in the Covid Pandemic period 19. This study used a qualitative method through interactional communication models. Data collection is done through observation, interviews, focus groups, and literature studies. The results of this study are the spirit of da'wah in the pandemic era using YouTube. The rise of the Covid 19 pandemic, which has killed thousands of people in the world, is so frightening to most people that the government implements regional closure, PSBB (large-scale social restrictions), and quarantine of such areas to break the spread of the Corona Virus. But in the middle of the holy month of Ramadan preaching activities are usually more intense because in this month Muslims want to flock to improve themselves and increase charity. Islam and da'wah are two inseparable things. Islam will not advance and develop brilliant and shining without the efforts of da'wah. The more vigorous the da'wah efforts are carried out the more cheerful the Islamic religion is, the slacker the da'wah efforts the fainter the light of Islam in society, Latsaal Islam illa bi al-da 'wah.